Understanding Chronic Kidney Disease- Mineral Bone Disorder (CKD-MBD) - Wan Ali, Wan Ahmad Syahril Rozli (2018)
Chronic kidney disease (CKD) is commonly associated with disorders of mineral and bone metabolism, manifested by either one or a combination of the following three components namely : Abnormalities of calcium, phosphorus, parathyroid hormone (PTH), fibroblast growth factor 23 (FGF23), and vitamin D metabolism; Abnormalities in bone turnover, mineralization, volume linear growth, or strength; and Extraskeletal calcification. This topic reviews the pathogenesis of CKD-MBD.